Accurate identification of bioactive meliaceae limonoids by UHPLC-MS/ms based structure-fragment relationships (SFRs) - Mulani, Fayaj A.; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, V, Hirekodathakallu (ACS Omega, 2021)
Y Limonoids are bioactive plant specialized metabolites found in the Meliaceae family. The basic limonoids, i.e., azadiradione, epoxyazadiradione, and gedunin have been exploited for various bioactivities and therefore are the potential drug leads for tomorrow. However, their low abundance, structural similarity, and lack of adequate mass fragmentation data have hampered their accurate identification and quantification from various sources. In the present study, basic limonoids such as azadirone, azadiradione, epoxyazadiradione, and gedunin isolated from Neem were utilized for the synthesis of their derivatives and isotopologs. A total of 30 one compounds were used in this study among which five were isolated, two were biotransformed, and 24 were synthesized. Among the synthesized compounds nine are novel compounds including six deuterated analogs/isotopologs which are (1,3-H-2)-1,2dihydro-3 beta-hydroxyazadiradione (9), (1,3,16-H-2)-1,2-dihydro-3 beta-16 beta-dihydroxyazadiradione (10), 3 beta-hydroxyazadiradione (11), 3 beta-16 beta-dihydroxyazadiradione (12), (3-H-2)-3 beta-hydroxyazadiradione (13), (3,16-H-2)-3 beta-16 beta-dihydroxyazadiradione (14), (1,3,7-H-2)-1,2-dihydro-3 beta-hydroxy-7-deacetylazadiradione (15), 1,2,20,21,22,23-hexahydroazadiradione (17), and (1,3-H-2)-1,2-dihydro-3 beta-hydroxygedunin (29). These limonoids along with their semisynthesized derivatives were subjected to ultra high performance liquid chromatography mass spectrometry (UHPLC-MS/MS) and the fragmentation pathway was established based on structure-fragment relationships (SFRs), utilizing high resolution MS/MS data. We have developed a most reliable and easily reproducible protocol describing in depth analysis of SFRs based on the structural modifications and synthesis of isotopologs. Also, the MS/MS fragment library of these basic limonoids generated in this study acts as a fingerprint for accurate identification and quantification of limonoids by MS/MS analysis in various plant tissue extracts, phytopharmaceutical formulations and biological samples.

Dynamic coupling analysis on plant sesquiterpene synthases provides leads for the identification of product specificity determinants - Singh, Sneha; Thulasiram, V, Hirekodathakallu; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2021)
Sesquiterpene synthases catalyse cyclisation of farnesyl pyrophosphate to produce diverse sesquiterpenes. Despite utilising the same substrate and exhibiting significant sequence and structural homology, these enzymes form different products. Previous efforts were based on identifying the effect of divergent residues present at the catalytic binding pocket on the product specificity of these enzymes. However, the rationales deduced for the product specificity from these studies were not generic enough to be applicable to other phylogenetically distant members of this family. To address this problem, we have developed a novel approach combining sequence, structural and dynamical information of plant sesquiterpene synthases (SSQs) to predict product modulating residues (PMRs). We tested this approach on the SSQs with known PMRs and also on sesquisabinene synthase 1 (SaSQS1), a SSQ from Indian sandalwood. Our results show that the dynamical sectors of SSQs obtained from molecular dynamics simulation and their hydrophobicity and vicinity indices together provide leads for the identification of PMRs. The efficacy of the technique was tested on SaSQS1 using mutagenesis. To the best of our knowledge, this is a first technique of this kind which provides cues on PMRs of SSQs, with divergent phylogenetic relationship. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: molecular dynamics; Product specificity; Sesquiterpene synthases; Statistical coupling analysis; X-ray crystallography

Synthetic heparan sulfate ligands for vascular endothelial growth factor to modulate angiogenesis - Jain, Prashant; Shanthamurthy, Chethan D.; Leviatan Ben-Arye, Shani; Yehuda, Sharon; Nandikol, Sharvani S.; Thulasiram, V, Hirekodathakallu; Padler-Karavani, Vered; Kikkeri, Raghavendra (Chemical Communications, 2021)
We report the discovery of a potential heparan sulfate (HS) ligand to target several growth factors using 13 unique HS tetrasaccharide ligands. By employing an HS microarray and SPR, we deciphered the crucial structure-binding relationship of these glycans with the growth factors BMP2, VEGF(165), HB-EGF, and FGF2. Notably, GlcNHAc(6-O-SO3-)-IdoA(2-O-SO3-) (HT-2,6S-NAc) tetrasaccharide showed strong binding with the VEGF(165) growth factor. In vitro vascular endothelial cell proliferation, migration and angiogenesis was inhibited in the presence of VEGF(165) and HT-2,6S-NAc or HT-6S-NAc, revealing the potential therapeutic role of these synthetic HS ligands.